Pyloric perforation due to stress disorders in an adolescent girl - Ahmet Atıcı; Mehmet Emin Çelikkaya; Çiğdem El; Bülent Akçora (Elsevier, 2018)
Gastroduodenal perforation is a serious emergency condition. The predominance of duodenal perforation in pediatric age group shifts towards gastric perforation at later ages. However, due to thick muscle tissue pyloric perforation is seen very rarely in all age groups [3]. A 14-year-old female patient with abdominal pain lasting for one day admitted to our pediatric emergency room. During the physical examination, generalized abdominal tenderness and muscular defense were observed in all quadrants of the abdomen. Laparotomy was performed with an upper abdominal median incision. A large amount of serous, non-biliary fluid was observed in the abdomen. A perforation area of nearly 3 mm was identified on the anterior of the pylorus. Primary repair with omentopexy of the pyloric perforation was performed. On postoperative day 7, the patient was discharged without any complication. Pyloric perforation should be considered in the differential diagnosis of patients presented with epigastric pain.